The Impact of Total Quality Management on Supply Chain Management in Five-Star Hotels in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2024)
The research investigates the impact of Total Quality Management (TQM) on Supply Chain Management (SCM) in five-star hotels in Saudi Arabia, focusing on how integrating TQM principles can enhance operational efficiency, reduce costs, and improve customer satisfaction within the hospitality sector. The study emphasizes the convergence of TQM and SCM, highlighting continuous improvement, a culture of quality, and customer satisfaction as key impacts of TQM on SCM. TQM encourages organizations to evaluate and enhance processes continuously, leading to more streamlined and efficient supply chains. The integration of TQM principles into SCM processes aims to achieve higher levels of customer satisfaction, improved product quality, reduced costs, and increased operational efficiency. Several challenges in implementing TQM in Saudi five-star hotels are identified, including communication barriers, resistance to change, and resource constraints. The study proposes a comprehensive strategy for successful TQM and SCM integration, emphasizing leadership commitment, employee involvement, and the use of advanced technologies for real-time data sharing and performance monitoring. The findings are significant for hotel managers and decision-makers, providing evidence-based recommendations for implementing TQM principles to optimize supply chain processes. By adopting TQM practices, five-star hotels in Saudi Arabia can enhance their operational performance, achieve cost optimization, and ensure high levels of customer satisfaction, ultimately gaining a competitive advantage in the dynamic hospitality industry
Keywords: Total Quality Management; Supply Chain Management; Hotels; KSA